Death and dying: The perception of nursing students during their education - Wachter , Djulia Andriele; Machado , Elisiane de Oliveira; Kerschner, Cíntia Letícia de Negreiros; Vizini , Simone Thais; Inchauspe , Juciane Aparecida Furlan; Reis, Fernanda dos; Santos , Suimara; Chassot , Maicon Daniel; Alves , Evelyn Tavares; Machado , Raquel Adjane (Seven Editora, 2023)
Of human experience , death has a special significance , because in front of her are led to reflect, it seems that our life is paralyzed for a moment . It is a subject still poucodiscutido and often ignored . It is a moment that encompasses anxiety , separation and pain, so many prefer to ignore reality and the fact that this time will one day come . Currently , the majority of deaths occur in hospitals , a reality which highlights the importance of the role of nursing in front of the family and the patient who is about to depart . For this assistance and understanding occur safely by the health professional , the preparation should start from the moment of graduation . Thus , the research aimed to understand the perceptions of students of nursing about the death during their training in a teaching institution . This is a descriptive research approach of qualitative analysis , in which students of Nursing Regional University of Blumenau were interviewed based on a semi-structured interview and recording of same . The survey was conducted from August to November 2013. All academic interviewees signed a consent form , occurred after approval by the ethics committee of the regional university of Blumenau with the opinion number 310 472 . The results of this research showed that nursing students interviewed are not adequately prepared to face the process of death and dying . Those who prepared reports show that this was because his professional experience , but not the knowledge acquired during their studies , the subjects recall the times when the subject was addressed , but in a very succinct and without further reflection . The role is to support graduate students coping with family , providing comfort and care to a death with respect and dignity , but realize that graduation is not enough to prepare the academic altogether. DOI:https://doi.org/10.56238/sevened2023.006-004